The Implementation of the Doblin Innovation Model in Strengthening Competitive Advantage at Islamic Religious Higher Education Institutions in Madura - Warits, Abd. (Belajea: Jurnal Pendidikan Islam, 2024)
This study examines the implementation of the Doblin Innovation Model in Islamic higher education institutions in Madura within the context of increasingly complex and dynamic educational challenges. The aim of this research is to analyze how the implementation of the Doblin Innovation Model is carried out to strengthen the competitive advantage of two institutions: Universitas Annuqayah and IAIN Madura. The methodology used is descriptive qualitative with a case study approach, involving the collection of primary data through in-depth interviews with relevant parties and secondary data from institutional documents. The findings indicate that the success of innovation implementation heavily depends on supporting factors such as leadership commitment, the availability of technology, and an open organizational culture. Additionally, the implementation of the Doblin Innovation Model is carried out through three models of innovation: the network model, the structural model, and the service model. These three models are integratively applied within the systems developed by each institution